Analysis of Strategic Factors for Successful Integrated System Implementation: Experiences from the Co-operative University of Kenya - Ngala, Orucho Michael (Archives of Business Research, 2023)
An integrated resource planning (ERP) system is essential for automation of manual routine tedious organizational processes. It is meant to improve efficiency and effectiveness at work. However, implementation of such systems, if not properly organized and appropriate strategies put in place to ensure its success, may take unnecessarily longer time than anticipated, or the whole system abandoned all together. This study sought to establish the most effective strategies that ensure successful and timely integrated system implementation. Systems theory and Process theory approaches were used to anchor the study. Case study was adopted as the research design. The population of the study comprised twelve (12) departments within Co-operative University of Kenya where different system modules were rolled out for implementation. Primary data was collected using semi-structured questionnaires. Since data collected was largely categorical in nature, Chi-square was used to analyze relationship between variables. It was established that personal interest and optimism is the most influential strategy in determining success and pace in integrated system implementation. The key recommendation that the study offers as insight to policy makers, body of theory and practitioners is the need to deliberately concentrate on strategies that induce personal interest and optimism among employees so as to ensure success during implementation of a new system or change.